PENGELOMPOKAN KABUPATEN/KOTA DI JAWA TENGAH MENGGUNAKAN METODE K-MEANS DAN FUZZY C-MEANS - Rahman Hidayat; Rochdi Wasono; Moh. Yamin Darsyah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The Poverty is still a serious problem, especially in Indonesia. Central Java is the province with the highest percentage of poor people in Java Island 13, 19%,the figure is above the national poverty rate. In this research will be an analysisof the factors affecting poverty in Central Java. The statistical approach used inthis case is cluster analysis. Cluster analysis is an analysis that aims to classifyan object (region) based on similarity characteristics of data. The method usedis the method of K-Means and Fuzzy C-Means. The object of research isgrouped into 4 clusters. The result of grouping shows that K-Means method isthe best method based on SW and SB ratio of 0.124. Keywords: Data Mining, K-means, Fuzzy C-Means